Breaking the paradigm: Optimized Case Finding multiplies tuberculosis detection among key populations in Ukraine - Liliia Masiuk; Olga Denisiuk; Evgenia Geliukh; Zahedul Islam; Garry Aslanyan; Rony Zachariah (Journal of Infection in Developing Countries)
Introduction: In 2018, there were 3 million “missed” tuberculosis (TB) cases globally, much of which was disproportionally concentrated among key populations. To enhance TB case-finding, an Optimized Case Finding (OCF) strategy involving all contacts within the social network of an index TB case was introduced in five regions of Ukraine. We assessed TB detection and linkage to TB treatment using OCF in key populations.